Magnitude of thyroid dysfunction among antenatal women attending tertiary care centre - Shanmugham, Deepa; Saravanan, Deepak Kannan; Shah, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Thyroid disorders constitute one of the most common endocrine disorders in pregnancy. However, there is no universal guidelines to screen every Pregnant Woman for Thyroid dysfunction in India. This study was conducted to evaluate the magnitude of thyroid dysfunction among ante natal mothers in a tertiary care centre. Methods: This was a cross sectional observational study conducted on ante natal mothers for a period of 6 months. All consecutive ante natal mothers in their first trimester were included in this study. Exclusion criteria was pre-gestational thyroid dysfunction, hypertension and diabetes mellitus. After obstetric examination and investigation, thyroid function test (Free T4 and TSH) was done in all patients. Results: Mean age of the patients enrolled was 26.2±3.54 years. Mean gestational age at which they underwent screening was 9±2 weeks. The mean BMI of the study patients was 21.7±4. The prevalence of hypothyroidism in antenatal mothers was 14.5%. 5 patients (5.5%) had hyperthyroidism. The calculated mean TSH value was 4.26 mIU/L. Conclusions: Universal screening for thyroid dysfunction during pregnancy should be made mandatory in India due to high prevalence, in order to prevent maternal and foetal complications.